Sleep Optimization in the Young Athlete: Current Concept Review - Imbergamo, Casey; Patankar, Aneesh; Milewski, Matthew (Journal of the Pediatric Orthopaedic Society of North America, 2021)
Young athletes commonly suffer from both acute and chronic sleep deprivation. This has been linked to increased injury rates and decreased athletic and neurocognitive performance. Conversely, sleep optimization in young athletes can lead to improved athletic performance and greater competitive success, with improvement in metrics such as speed, endurance, reaction time, accuracy, alertness, and overall well-being. When aiming to optimize sleep, key elements such as sleep duration, quality, and regularity must be addressed. Clinicians can assess baseline sleep hygiene in young athletes, and educate them on proper methods to optimize sleep. Such methods include limiting screen time before bed, getting exposure to sunlight in the early morning, maintaining an optimal bedroom temperature, avoiding caffeine, and maintaining a consistent sleep schedule throughout the week.